Relationship between Emotional and Spiritual Intelligence Levels with Non-Suicidal Self-Injury (NSSI) Behaviour in Adolescents during COVID-19 Pandemic - Nugrahawati, Lelly Resna; Nuripah, Gemah; Budiyanti, Lina; Afifah, Nur Azmi; Lestari, Avinindita Nura (Global Medical & Health Communication (GMHC), 2023)
The problem of growth and development in adolescence and the emergence of the COVID-19 pandemic is psychosocial stress that could trigger anxiety, depression, and non-suicidal self-injury (NSSI). This research aims to describe the relationship between the level of emotional intelligence and spiritual intelligence with NSSI behavior in adolescents. We conducted quantitative correlational research with a cross-sectional approach. Subjects in the study consist of high school students in Bandung from June 2021 to July 2021. The examination was carried out through a questionnaire of Self-Harm Inventory (SHI) instrument, the emotional intelligence scale, and the spiritual intelligence scale. Sixty respondents with NSSI behavior were found (30.15%) out of 199 respondents, mostly aged 15–17 and female. Among them, 54 meet the mild NSSI behavior, and six people tend severe psychopathology. All adolescents with NSSI behavior were found to exhibit a level of emotional and spiritual intelligence in the moderate category. Statistically, there is a significant and simultaneous relationship between the level of emotional and spiritual intelligence and NSSI behavior in adolescents. Therefore, psychosocial intervention effort is essential for adolescents with NSSI to increase their spiritual and emotional intelligence. Adolescents with severe psychopathology need to be referred to a psychiatrist for further examination.